2020
DOI: 10.1002/pits.22449
|View full text |Cite
|
Sign up to set email alerts
|

Grit, fit, gender, and academic achievement among first‐year college students

Abstract: Academic achievement is a known predictor of career trajectory and future earnings. Thus, a great deal of research has been devoted to understanding the variables that impact academic achievement. The purpose of the current study is to extend existing scholarly work by examining the predictive power of both cognitive and noncognitive variables on first-year academic achievement of students at a military college. We focus on the concepts of grit and person-environment (P-E) fit as our key noncognitive predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Hence, students' engagement in SRL may function as a mediating pathway through which this aspect of grit is associated with enhanced academic outcomes. Evidence for the impact of grit on academic success has thus far been mixed (Whipple and Dimitrova-Grajzl 2021). The current research also explores this relationship and further determines whether grit and self-regulated learning together would form the basis of good performance in schools.…”
Section: Grit Srl and Academic Outputmentioning
confidence: 91%
“…Hence, students' engagement in SRL may function as a mediating pathway through which this aspect of grit is associated with enhanced academic outcomes. Evidence for the impact of grit on academic success has thus far been mixed (Whipple and Dimitrova-Grajzl 2021). The current research also explores this relationship and further determines whether grit and self-regulated learning together would form the basis of good performance in schools.…”
Section: Grit Srl and Academic Outputmentioning
confidence: 91%
“…A great deal of research has been carried out to understand the variables affecting academic achievement. However, only a few studies have focused on the role of gender in predicting a student's academic success (Whipple and Dimitrova-Grajzl, 2021 ). Female students not only surpassed their male counterparts in academic achievement but also in classroom activities and participation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it needs to be explored further in the socio-cultural context (Mathew et al, 2013 ; Fallan and Opstad, 2016 ). According to Whipple and Dimitrova-Grajzl ( 2021 ), gender has a significant role in academic achievement. They maintain that male learners achieve higher grades compared to female learners, who have a moderate effect on their learning in the presence of the opposite gender.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In more recent studies (Ma et al, 2020;Whipple and Dimitrova-Grajzl, 2021) researchers looked at the effects of grit on male and female students and found that there were significant gender differences in the effects of grit. According to the findings of Ma, Ma, and Lan, higher levels of grit have a beneficial effect on both males and females with regard to the association between teacher autonomy support and social competence.…”
Section: Research On Gritmentioning
confidence: 99%